Development of a standardized single-session cardiopulmonary exercise test for combined assessment of peak oxygen uptake and on/off-kinetics - Santana, J. L.; Enzner, T.; Blunderfield, B.; Mendelson, A. A.; Villar, R. (Experimental Physiology, 2025)
Peak oxygen uptake (VO2peak) and VO2 on/off-kinetics are key indicators of exercise capacity and health outcomes, but their assessment often requires separate laboratory visits, which limits feasibility. This cross-sectional study aimed to develop a single cardiopulmonary exercise test (CPET) for both assessments. We designed a single-session combined CPET protocol using an upright cycle ergometer in healthy volunteers (n = 20). VO2peak was first estimated using an a priori formula. The constant work rate (CWR) part of the test (on-kinetics) was set to an intensity of 30% VO2reserve. After an incremental test to measure VO2peak, a 10-min recovery period was used to evaluate off-kinetics. Twenty volunteers (9 females and 11 males), 28.0 ± 8.1 years, completed the protocol. No significant differences were found between predicted and measured VO2peak (P = 0.47). A strong correlation (r = 0.88) and good agreement (Bland-Altman bias = -0.82 mL·kg¹·min¹) were found between the calculated/actual individuals` 30% VO2reserve (mL·kg¹·min¹) and the measured steady-state VO2 at CWR. The measured exercise intensity at CWR closely matched the target of 30%, with no statistical differences, with an average difference of 0.2 percentage points. Small-medium Cohen`s d (0.16) indicated high similarity between predicted and measured VO2peak. VO2 on- and off-kinetics analyses were also performed for all participants with mono-exponential fittings. A single-session protocol for the combined assessment of VO2peak and VO2 on/off-kinetics was developed. This protocol will enable greater recruitment and participation in research and enhanced detail for clinical CPET use. Future research should evaluate intra- and inter-participant reproducibility over repeated sessions.